2016
DOI: 10.7717/peerj.2407
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure and diversity of the selfing model grassBrachypodium stacei(Poaceae) in Western Mediterranean: out of the Iberian Peninsula and into the islands

Abstract: Annual Mediterranean species of the genus Brachypodium are promising model plants for energy crops since their selfing nature and short-life cycles are an advantage in breeding programs. The false brome, B. distachyon, has already been sequenced and new genomic initiatives have triggered the de-novo genome sequencing of its close relatives such as B. stacei, a species that was until recently mistaken for B. distachyon. However, the success of these initiatives hinges on detailed knowledge about the distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 71 publications
6
17
0
Order By: Relevance
“…Similar results are reported for gene diversity statistics (Nei and Chesser 1983) (Table 4), which indicates that 86.4% of the total diversity is partitioned among populations (GST = 0.864). This level of genetic differentiation among populations of V. dubia is greater than that reported for invasive populations of other selfing grass species such as B. tectorum (Novak and Mack 2016) and Brachypodium stacei (Shiposha et al 2016), but very similar to the level reported for T. caput-medusae (GST = 0.907) (S.J. Novak, unpublished data).…”
Section: Genetic Diversity and Genetic Structuresupporting
confidence: 68%
“…Similar results are reported for gene diversity statistics (Nei and Chesser 1983) (Table 4), which indicates that 86.4% of the total diversity is partitioned among populations (GST = 0.864). This level of genetic differentiation among populations of V. dubia is greater than that reported for invasive populations of other selfing grass species such as B. tectorum (Novak and Mack 2016) and Brachypodium stacei (Shiposha et al 2016), but very similar to the level reported for T. caput-medusae (GST = 0.907) (S.J. Novak, unpublished data).…”
Section: Genetic Diversity and Genetic Structuresupporting
confidence: 68%
“…3). Previous studies with similar plant distributions in the eastern Iberian Peninsula and Balearic Islands also identify the mainland as the area of origin (Prentice et al, 2003;Juan et al, 2012;Garnatje et al, 2013;Shiposha et al, 2016).…”
Section: Discussion Phylogeographical History Of Carduncellus Dianiusmentioning
confidence: 78%
“…The active history of multiple colonizations in C. dianius could have meant the erosion of part of its genetic diversity at each colonization step (due to founder effects) as other studies reported (e.g. Shiposha et al, 2016). In addition, the restricted seed dispersal and the reduced inter-population gene flow (Table S5) would have fostered the predominance of drift, which has been reported as one of the main evolutionary forces to explain the high plant diversity in the Mediterranean area (Rosselló, 2013 and references therein).…”
Section: Phylogeographical Patterns Shaping Genetic Variation and Strmentioning
confidence: 90%
“…occurs in ephemeral aquatic ponds probably further reduces the probability of gene flow between them. The absence of genetic variation within populations observed in this study is not uncommon in highly autogamous plants (e.g., Shiposha & al., ; Marques & al., ).…”
Section: Discussionmentioning
confidence: 99%